2015
DOI: 10.1037/a0038056
|View full text |Cite
|
Sign up to set email alerts
|

Associations between color and shape in Japanese observers.

Abstract: Albertazzi et al. (2013) showed naturally biased associations between geometric shapes and colors in Italian participants, suggesting that the "warmth" and "lightness" of color might account for the color-shape associations. In the present study, we replicated the previous study in Japanese participants to examine whether color-shape associations were unlikely influenced by differences between languages and cultures. Results showed that Japanese participants associated shapes with specific colors, and these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
93
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(104 citation statements)
references
References 45 publications
10
93
0
1
Order By: Relevance
“…Finally, it would be interesting to repeat the experiment in other contexts and with different people. For that matter, a recent experiment conducted in Japan (Chen et al, 2013), which used the design of our previous research on the association between shapes and colours (Albertazzi et al, 2013), has obtained similar results.…”
Section: Discussionmentioning
confidence: 62%
“…Finally, it would be interesting to repeat the experiment in other contexts and with different people. For that matter, a recent experiment conducted in Japan (Chen et al, 2013), which used the design of our previous research on the association between shapes and colours (Albertazzi et al, 2013), has obtained similar results.…”
Section: Discussionmentioning
confidence: 62%
“…A number of studies have empirically examined the color‐form assignment proposed by Kandinsky using a direct matching or implicit test such as IAT, and their results are summarized in Table . Although there are some exceptions, a triangle tended to be associated with yellow by Italian and Japanese people and by art experts in the study of Jacobsen and Wolsdorff . This association was also observed in this study.…”
Section: Discussionmentioning
confidence: 96%
“…6 Chen et al also reported evidence that warmnesscoolness mediated color-shape associations in Japanese people, though they also acknowledged that world-knowledge associations also affect their results. 7 Malfatti et al also reported that emotions, especially anger and sadness/happiness, can explain color-shape associations. 15 However, this study did not find any particular emotional dimensions mediating the color-form associations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…La repercusión de estos trabajos en el ámbito de la Academia -en cuanto al estudio de estas correlaciones entre alumnado educado en teoría del diseño y aquellos que no lo están, ha hecho que se lleven a cabo diversas réplicas de los mismos (Kharkhurin, 2012; Holmes y Zanker, 2013; Makin y Wuerger, 2013, Brooks, 2016; Walter 2018) e, incluso, en ámbitos con una tradición visual no occidental, como el desarrollado en Japón y China por Chen et al (2015a;2015b;2016, 2019.…”
Section: El Cuestionario De Kansdinsky Desde La Actualidadunclassified